Preparation method of water-based binder, water-based binder and application of water-based binder
By using an aqueous binder in a lithium battery, a three-dimensional network structure is formed through the condensation reaction of polymers and small molecule organic acids, and adsorbing silicon-based negative electrode materials through hydrogen bonds, the problems of easy powderization and poor circulation performance of silicon particles are solved, the performance of lithium batteries is improved and toxic solvents are replaced.
Patent Information
- Application Number
- CN202311223413.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-20
- Publication Date
- 2025-03-21
AI Technical Summary
When existing binders are used in lithium batteries, silicon particles are prone to powdering and circulation performance, and the solvent NMP is toxic and volatile, resulting in environmental pollution.
Using an aqueous binder, a three-dimensional network structure is formed by condensation reaction between component A (a polymer containing carboxyl and hydroxyl groups) and component B (a small molecule organic acid containing carboxyl or hydroxyl groups). Component B adsorbs the silicon-based anode material through hydrogen bonds and forms a passivation layer.
It effectively avoids the problems of powdering and poor circulation performance of silicon-based negative electrode materials, improves the first week of the Coulomb efficiency and cycle stability of lithium batteries, and replaces toxic solvents, which is environmentally friendly and feasible.
Smart Images

Figure CN119674073A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium battery materials, and in particular to a preparation method of a water-based binder, the water-based binder and applications thereof. Background Art
[0002] The huge volume expansion of silicon-based negative electrode materials during the cycle process can lead to the pulverization of silicon particles, the separation of electrode active substances and conductive particles, and the cracking of electrode structures. To address these problems, researchers have improved them by designing new silicon structures and developing new electrolytes and binders.
[0003] Currently, the main commercial binder is polyvinylidene fluoride (PVDF). The solvent of the binder, N-methylpyrrolidone (NMP), is toxic and volatile, which will pollute the environment. In addition, the battery assembled with the negative electrode made of polyvinylidene fluoride and silicon-based negative electrode materials has the defects of easy pulverization of silicon particles and poor battery cycle performance. Therefore, it is necessary to develop a new water-based binder to replace PVDF. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing an aqueous binder, an aqueous binder and its application, so as to solve the problems that when existing binders such as polyvinylidene fluoride are used in lithium batteries with silicon negative electrode materials, silicon particles are easily pulverized and have poor cycle performance, and the solvent NMP used in the binder is toxic and volatile.
[0005] To this end, in a first aspect, an embodiment of the present invention provides a water-based binder, the water-based binder comprising component A and component B;
[0006] Wherein, the component A is a polymer containing carboxyl and hydroxyl groups in the molecular formula; the component B is a small molecule organic acid containing carboxyl or hydroxyl groups in the molecular formula;
[0007] The component A and the component B undergo a condensation reaction to form a three-dimensional network structure;
[0008] The mass ratio of component A to component B is [1:9]-[9:1];
[0009] The aqueous binder is used in the negative electrode of the lithium battery, and the component B adsorbs the silicon-based negative electrode material of the negative electrode through hydrogen bonds and covers the surface of the silicon-based negative electrode material to form a passivation layer.
[0010] Preferably, the component A specifically includes: one or more of sodium carboxymethyl cellulose, polyacrylic acid, sodium alginate, polyvinyl alcohol, and carboxymethyl chitosan.
[0011] Preferably, the component B comprises: one or more of tartaric acid, citric acid, oxalic acid, fumaric acid, maleic acid and malic acid.
[0012] In a second aspect, an embodiment of the present invention provides a method for preparing the water-based binder according to the first aspect, the preparation method comprising:
[0013] Component A is prepared into an aqueous solution with a mass fraction of 1% to 5%, and then a certain amount of component B is added, and the mixture is heated and stirred in a water bath to be uniformly mixed to obtain a mixed solution;
[0014] The mixed solution is placed in a container with a polytetrafluoroethylene substrate, and placed in a vacuum drying oven for drying to obtain a block precursor;
[0015] The block precursor is put into a mortar, ground and sieved to obtain a water-based binder.
[0016] Preferably, the component A is a polymer containing carboxyl and hydroxyl groups in the molecular formula, specifically including: sodium carboxymethyl cellulose, polyacrylic acid, sodium alginate, polyvinyl alcohol, carboxymethyl chitosan or one or more thereof.
[0017] The component B is a small molecule organic acid containing a carboxyl group or a hydroxyl group in the molecular formula, specifically including: one or more of tartaric acid, citric acid, oxalic acid, fumaric acid, maleic acid, and malic acid;
[0018] The mass ratio of the component A to the component B in the mixed solution is [1:9]-[9:1].
[0019] Preferably, the drying conditions are as follows: drying in a vacuum drying oven at 90°C-120°C for 5 hours-8 hours;
[0020] The conditions for the water bath heating and stirring are specifically: the heating temperature is 85° C.-95° C., and the time is 6 hours-10 hours.
[0021] In a third aspect, an embodiment of the present invention provides a negative electrode, which includes a negative electrode active material, the aqueous binder described in the first aspect, and a conductive agent.
[0022] Preferably, the negative electrode active material is a silicon-based negative electrode material, specifically including: any one of nano-silicon, silicon-carbon composite material, and silicon oxide; the conductive agent includes: one or more of acetylene black, carbon nanotubes, Ketjen black, conductive graphite, and graphene;
[0023] The mass percentages of the negative electrode active material, the conductive agent, and the aqueous binder are [80%-95%]:[3%-10%]:[2%-10%].
[0024] In a fourth aspect, an embodiment of the present invention provides a lithium battery, comprising a positive electrode, the negative electrode described in the third aspect, an electrolyte or a solid electrolyte, and a separator.
[0025] Preferably, the lithium battery includes: any one of a lithium-ion battery, a lithium-sulfur battery, and an all-solid-state battery.
[0026] The embodiment of the present invention provides a preparation method of an aqueous binder, an aqueous binder and an application thereof, wherein a polymer containing carboxyl and hydroxyl groups is mixed with a small molecule organic acid containing carboxyl or hydroxyl groups to generate a condensation reaction to form a three-dimensional network structure, wherein the small molecule organic acid adsorbs silicon of a silicon-based negative electrode material through hydrogen bonds, thereby achieving a coating effect on the silicon-based negative electrode material and forming a passivation layer, thereby avoiding or reducing the direct contact between silicon in the silicon-based negative electrode material and an electrolyte to generate a solid electrolyte interface film (SEI) that affects the cycle performance; the aqueous binder provided by the embodiment of the present invention, on the one hand, the hydrogen bonds of the small molecule organic acid act like a "sucker" and act on the surface of the silicon-based negative electrode material to form a passivation layer, which can effectively avoid the occurrence of side reactions, thereby reducing capacity loss and avoiding SEI generation, thereby improving the first-cycle coulomb efficiency and cycle performance; on the other hand, the formed three-dimensional network structure has good mechanical properties, can inhibit the volume expansion of the silicon-based negative electrode material, avoid the problem of pulverization, thereby further improving the cycle stability; the aqueous binder of the present invention is applied to a lithium battery, which can effectively improve the first-cycle coulomb efficiency and cycle stability of the lithium battery.
[0027] The method for preparing a water-based binder provided in an embodiment of the present invention is simple to operate, applicable to large-scale production, and has practical significance for industrial applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] The technical solution of the embodiment of the present invention is further described in detail below through the drawings and examples.
[0029] Figure 1 It is a flow chart of a method for preparing a water-based binder provided in an embodiment of the present invention. DETAILED DESCRIPTION
[0030] The present invention is further described in detail below through the accompanying drawings and specific embodiments, but it should be understood that these embodiments are only used for more detailed description and should not be understood as limiting the present invention in any form, that is, they are not intended to limit the protection scope of the present invention.
[0031] The embodiment of the present invention provides a water-based adhesive, the water-based adhesive comprising component A and component B;
[0032] Among them, component A is a polymer containing carboxyl and hydroxyl groups in the molecular formula; component B is a small molecule organic acid containing carboxyl or hydroxyl groups in the molecular formula; the mass ratio of component A to component B is [1:9]-[9:1], preferably 1:1; component A and component B undergo condensation reaction to form a three-dimensional network structure.
[0033] The aqueous binder provided in the embodiment of the present invention is used in the negative electrode of a lithium battery. Component B in the aqueous binder adsorbs the silicon-based negative electrode material of the negative electrode through hydrogen bonds and is coated on the surface of the silicon-based negative electrode material to form a passivation layer.
[0034] Specifically, component A includes: one or more of sodium carboxymethyl cellulose, polyacrylic acid, sodium alginate, polyvinyl alcohol, and carboxymethyl chitosan.
[0035] Component B includes: one or more of tartaric acid, citric acid, oxalic acid, fumaric acid, maleic acid and malic acid.
[0036] The present invention provides a method for preparing the above-mentioned water-based binder, such as Figure 1 As shown, the specific steps include:
[0037] Step 110, preparing component A into an aqueous solution with a mass fraction of 1% to 5%, then adding a certain amount of component B, heating and stirring in a water bath, mixing evenly, and obtaining a mixed solution;
[0038] Component A is a polymer containing carboxyl and hydroxyl groups in the molecular formula, specifically including: sodium carboxymethyl cellulose, polyacrylic acid, sodium alginate, polyvinyl alcohol, carboxymethyl chitosan or one or more thereof.
[0039] Component B is a small molecule organic acid containing a carboxyl group or a hydroxyl group in the molecular formula, specifically including: one or more of tartaric acid, citric acid, oxalic acid, fumaric acid, maleic acid, and malic acid;
[0040] The mass ratio of component A to component B in the mixed solution is [1:9]-[9:1];
[0041] The conditions for water bath heating and stirring are as follows: heating temperature is 85° C.-95° C., and time is 6 hours-10 hours.
[0042] Step 120, placing the mixed solution in a container with a polytetrafluoroethylene substrate, and placing it in a vacuum drying oven for drying to obtain a block precursor;
[0043] The specific conditions for the drying treatment are: drying in a vacuum drying oven at 90° C. to 120° C. for 5 hours to 8 hours.
[0044] Step 130, grinding and sieving the block precursor in a mortar to obtain a water-based binder;
[0045] The grinding and sieving in the preparation method of the present invention are conventional methods known in the art.
[0046] An embodiment of the present invention provides a negative electrode comprising the above-mentioned aqueous binder, which is prepared by preparing a negative electrode slurry together with the aqueous binder prepared by the above-mentioned preparation method, a negative electrode active material, and a conductive agent, and then the negative electrode slurry is coated on a negative electrode collector, and then dried and cut to obtain a negative electrode.
[0047] Among them, the negative electrode active material is a silicon-based negative electrode material, specifically including: any one of nano-silicon, silicon-carbon composite materials, and silicon oxide; the conductive agent includes: one or more of acetylene black, carbon nanotubes, Ketjen black, conductive graphite, and graphene; the mass percentages of the negative electrode active material, the conductive agent, and the aqueous binder are [80%-95%]:[3%-10%]:[2%-10%].
[0048] An embodiment of the present invention provides a lithium battery, which includes a positive electrode, the above-mentioned negative electrode, an electrolyte or a solid electrolyte, and a separator; the lithium battery includes: any one of a lithium ion battery, a lithium sulfur battery, and an all-solid-state battery.
[0049] The positive electrode active material in the positive electrode includes, but is not limited to, any one of lithium iron phosphate, lithium cobalt oxide, lithium manganese oxide, lithium sulfide, nickel cobalt lithium manganese oxide, and sulfur-carbon composites.
[0050] The electrolyte or solid electrolyte and the diaphragm mentioned in the embodiments of the present invention are all conventional materials known in the art.
[0051] Applying the above-mentioned aqueous binder to lithium batteries can effectively improve the first-week coulomb efficiency and cycle stability of lithium batteries.
[0052] In order to better understand the technical solution provided by the present invention, the preparation process and characteristics of the water-based binder of the present invention are respectively described below with multiple specific examples.
[0053] Example 1
[0054] This embodiment provides a preparation process and performance test of a water-based binder. The specific preparation process is as follows:
[0055] (1) Sodium carboxymethyl cellulose is prepared into an aqueous solution with a mass fraction of 1%, and then tartaric acid is added, and the mixture is heated and stirred in a water bath at 90° C. for 6 hours and mixed to obtain a mixed solution; wherein the mass ratio of sodium carboxymethyl cellulose to tartaric acid is 1:1.
[0056] (2) The mixed solution is placed in a container with a polytetrafluoroethylene substrate, placed in a vacuum drying oven at 90° C. and dried for 8 hours, and then taken out to obtain a block precursor.
[0057] (3) The block precursor is placed in a mortar, ground, and sieved to obtain a water-based binder.
[0058] The negative electrode plates were prepared using the aqueous binder prepared in this example and assembled into CR2032 button cells for testing. The specific process is as follows.
[0059] First, the aqueous binder is dissolved in deionized water. After it is completely dissolved, the silicon-carbon composite material and the conductive agent acetylene black are added to prepare the negative electrode slurry; wherein, the mass ratio of the silicon-carbon composite material (capacity of 550 mAh / g), the aqueous binder, and the conductive agent acetylene black is 90:7:3; the negative electrode slurry is placed in a blender and stirred for 6 hours, coated on a copper foil, and then the copper foil coated with the negative electrode slurry is placed in a vacuum drying oven and dried at 80°C for 8 hours. After drying, it is taken out and cut into discs with a diameter of 12 mm by a cutting machine to prepare a negative electrode.
[0060] A lithium sheet with a diameter of 12 mm was used as the positive electrode; a solution of 1 mol / L Li PF6 in ethylene carbonate (EC) / diethyl carbonate (DEC) (the volume ratio of EC to DEC was 1:1) was used as the electrolyte; a polypropylene diaphragm was used as the diaphragm, and the CR2032 button battery was assembled in a glove box filled with argon (H2O < 0.01 ppm, O2 < 0.01 ppm).
[0061] The assembled CR2032 button battery was subjected to a cycle performance test using a blue power test system, with an initial activation current density of 0.1C and an operating voltage range of 0.005-1.5V, followed by a long cycle test at a current density of 0.5C.
[0062] The test data of initial efficiency and cycle capacity retention rate of the button cell prepared in this example are shown in Table 1.
[0063] Example 2
[0064] This embodiment provides a preparation process and performance test of a water-based binder. The specific preparation process is as follows:
[0065] (1) Polyacrylic acid is prepared into an aqueous solution with a mass fraction of 2%, and then citric acid is added, and the mixture is heated and stirred in a water bath at 95° C. for 5 hours and mixed evenly to obtain a mixed solution; wherein the mass ratio of polyacrylic acid to citric acid is 3:1.
[0066] (2) The mixed solution is placed in a container with a polytetrafluoroethylene substrate, placed in a vacuum drying oven at 80° C. and dried for 10 hours, and then taken out to obtain a block precursor.
[0067] (3) The block precursor is placed in a mortar, ground, and sieved to obtain a water-based binder.
[0068] The negative electrode plates were prepared using the aqueous binder prepared in this example and assembled into CR2032 button cells for testing. The specific process was the same as that in Example 1. The initial efficiency and cycle capacity retention test data are shown in Table 1.
[0069] Example 3
[0070] This embodiment provides a preparation process and performance test of a water-based binder. The specific preparation process is as follows:
[0071] (1) Carboxymethyl chitosan is prepared into an aqueous solution with a mass fraction of 2.5%, and then maleic acid is added, and the mixture is heated and stirred in a water bath at 95° C. for 7 hours and mixed evenly to obtain a mixed solution; wherein the mass ratio of carboxymethyl chitosan to maleic acid is 1:4.
[0072] (2) The mixed solution is placed in a container with a polytetrafluoroethylene substrate, placed in a vacuum drying oven at 100° C. and dried for 6 hours, and then taken out to obtain a block precursor.
[0073] (3) The block precursor is placed in a mortar, ground, and sieved to obtain a water-based binder.
[0074] The negative electrode plates were prepared using the aqueous binder prepared in this example and assembled into CR2032 button cells for testing. The specific process was the same as that in Example 1. The initial efficiency and cycle capacity retention test data are shown in Table 1.
[0075] Example 4
[0076] This embodiment provides a preparation process and performance test of a water-based binder. The specific preparation process is as follows:
[0077] (1) Polyvinyl alcohol is prepared into an aqueous solution with a mass fraction of 5%, and then fumaric acid is added, and the mixture is heated and stirred in a water bath at 100° C. for 4 hours and mixed evenly to obtain a mixed solution; wherein the mass ratio of polyvinyl alcohol to fumaric acid is 1:5.
[0078] (2) The mixed solution is placed in a container with a polytetrafluoroethylene substrate, placed in a vacuum drying oven at 95° C. and dried for 6 hours, and then taken out to obtain a block precursor.
[0079] (3) The block precursor is placed in a mortar, ground, and sieved to obtain a water-based binder.
[0080] The negative electrode plates were prepared using the aqueous binder prepared in this example and assembled into CR2032 button cells for testing. The specific process was the same as that in Example 1. The initial efficiency and cycle capacity retention test data are shown in Table 1.
[0081] Example 5
[0082] This embodiment provides a preparation process and performance test of a water-based binder. The specific preparation process is as follows:
[0083] (1) Sodium carboxymethyl cellulose is prepared into an aqueous solution with a mass fraction of 2%, and then maleic acid is added, and the mixture is heated and stirred in a water bath at 95° C. for 8 hours and mixed evenly to obtain a mixed solution; wherein the mass ratio of sodium carboxymethyl cellulose to maleic acid is 5:4.
[0084] (2) The mixed solution is placed in a container with a polytetrafluoroethylene substrate, placed in a vacuum drying oven at 100° C. and dried for 8 hours, and then taken out to obtain a block precursor.
[0085] (3) The block precursor is placed in a mortar, ground, and sieved to obtain a water-based binder.
[0086] The negative electrode plates were prepared using the aqueous binder prepared in this example and assembled into CR2032 button cells for testing. The specific process was the same as that in Example 1. The initial efficiency and cycle capacity retention test data are shown in Table 1.
[0087] Example 6
[0088] This embodiment provides a preparation process and performance test of a water-based binder. The specific preparation process is as follows:
[0089] (1) Carboxymethyl chitosan is prepared into an aqueous solution with a mass fraction of 2.5%, and then maleic acid is added, and the mixture is heated and stirred in a water bath at 90° C. for 6 hours and mixed evenly to obtain a mixed solution; wherein the mass ratio of carboxymethyl chitosan to maleic acid is 1:4.
[0090] (2) The mixed solution is placed in a container with a polytetrafluoroethylene substrate, placed in a vacuum drying oven at 100° C. and dried for 6 hours, and then taken out to obtain a block precursor.
[0091] (3) The block precursor is placed in a mortar, ground, and sieved to obtain a water-based binder.
[0092] The negative electrode plates were prepared using the aqueous binder prepared in this example and assembled into CR2032 button cells for testing. The specific process was the same as that in Example 1. The initial efficiency and cycle capacity retention test data are shown in Table 1.
[0093] Example 7
[0094] This embodiment provides a preparation process and performance test of a water-based binder. The specific preparation process is as follows:
[0095] (1) Sodium carboxymethyl cellulose is prepared into an aqueous solution with a mass fraction of 2%, and then tartaric acid is added, and the mixture is heated and stirred in a water bath at 90° C. for 8 hours, and mixed evenly to obtain a mixed solution; wherein the mass ratio of sodium carboxymethyl cellulose to tartaric acid is 1:1.
[0096] (2) The mixed solution is placed in a container with a polytetrafluoroethylene substrate, placed in a vacuum drying oven at 100° C. and dried for 8 hours, and then taken out to obtain a block precursor.
[0097] (3) The block precursor is placed in a mortar, ground, and sieved to obtain a water-based binder.
[0098] The negative electrode plates were prepared using the aqueous binder prepared in this embodiment and assembled into CR2032 button cells for testing. The specific process was the same as that in Example 1. The difference from Example 1 was that the negative electrode active material used in the preparation process of the negative electrode plates was silicon monoxide (capacity of 1650 mAh / g). The initial efficiency and cycle capacity retention test data are shown in Table 1.
[0099] Example 8
[0100] This embodiment provides a preparation process and performance test of a water-based binder. The specific preparation process is as follows:
[0101] (1) sodium carboxymethyl cellulose is prepared into an aqueous solution with a mass fraction of 1%, and then maleic acid is added, and the mixture is heated and stirred in a water bath at 100° C. for 8 hours, and mixed evenly to obtain a mixed solution; wherein the mass ratio of sodium carboxymethyl cellulose to maleic acid is 2:1.
[0102] (2) The mixed solution is placed in a container with a polytetrafluoroethylene substrate, placed in a vacuum drying oven at 100° C. and dried for 8 hours, and then taken out to obtain a block precursor.
[0103] (3) The block precursor is placed in a mortar, ground, and sieved to obtain a water-based binder.
[0104] The negative electrode plates were prepared using the aqueous binder prepared in this embodiment and assembled into CR2032 button cells for testing. The specific process was the same as that in Example 1. The difference from Example 1 was that the negative electrode active material used in the preparation process of the negative electrode plates was a nano-silicon material with a particle size Dv50 of 100 nm. The initial efficiency and cycle capacity retention test data are shown in Table 1.
[0105] To better illustrate the effects of the embodiments of the present invention, Comparative Example 1 is compared with Embodiments 1-6, Comparative Example 2 is compared with Embodiment 7, and Comparative Example 3 is compared with Embodiment 8.
[0106] Comparative Example 1
[0107] In this comparative example, the negative electrode plates were prepared using a traditional binder PVDF and assembled into CR2032 button cells for testing. The specific process was the same as that in Example 1. The initial efficiency and cycle capacity retention test data are shown in Table 1.
[0108] Comparative Example 2
[0109] In this comparative example, the negative electrode plates were prepared using a traditional binder PVDF and assembled into CR2032 button cells for testing. The specific process was the same as that of Example 7, and silicon dioxide was also used as the negative electrode active material. The initial efficiency and cycle capacity retention test data are shown in Table 1.
[0110] Comparative Example 3
[0111] In this comparative example, the negative electrode plates were prepared using the traditional binder PVDF and assembled into CR2032 button cells for testing. The specific process was the same as that in Example 8, and the negative electrode active material also used nano-silicon material with a particle size Dv50 of 100 nm. The initial efficiency and cycle capacity retention test data are shown in Table 1.
[0112] Table 1 is the test data of the batteries assembled with the binders prepared in Examples 1-8 and Comparative Examples 1-3: the first-cycle coulombic efficiency of button-type half-cells, and the capacity retention rate after 100 and 200 cycles, which are summarized as follows.
[0113]
[0114] Table 1
[0115] By comparing the data in Table 1, it can be seen that the first-week coulombic efficiency of the batteries of Examples 1-6 is improved compared with that of the batteries of Comparative Examples 1-3, the first-week coulombic efficiency of the battery of Example 7 is better than that of Comparative Example 2, and the first-week coulombic efficiency of the battery of Example 8 is better than that of Comparative Example 3; among them, compared with Comparative Example 3, the improvement of Example 8 is more obvious. This is because, for pure nano-silicon material, silicon particles are more exposed, so the adsorption, coating and passivation effect of small molecule acids on silicon particles is more obvious, so the first-week coulombic efficiency of the battery of Example 8 is relatively improved. The cycle capacity retention rates of the batteries of Examples 1-8 are all higher than those of the batteries of Comparative Examples 1-3. This is because: on the one hand, the small molecule acid and the polymer can form a bonding network with a large number of "sucker"-like hydrogen bonds. The small molecule acid adsorbs the silicon oxide layer on the surface of the silicon-based negative electrode material through hydrogen bonds and coats the surface of the silicon-based negative electrode material to form a passivation layer, avoiding or reducing the direct contact between the silicon in the silicon-based negative electrode material and the electrolyte to form a solid electrolyte interface film (SEI), thereby improving the cycle performance; on the other hand, the polymer can provide a strong skeleton required for the bonding network to avoid deformation or even pulverization of the electrode due to the volume stress generated by the active substance. The above results show that the battery using the aqueous binder provided by the embodiment of the present invention has been improved in terms of the first week coulomb efficiency and cycle stability, among which, when the negative electrode active material is nano-silicon, the effect is more obvious.
[0116] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A water-based adhesive, characterized in that: The water-based binder comprises component A and component B; Wherein, the component A is a polymer containing carboxyl and hydroxyl groups in the molecular formula; the component B is a small molecule organic acid containing carboxyl or hydroxyl groups in the molecular formula; The component A and the component B undergo a condensation reaction to form a three-dimensional network structure; The mass ratio of component A to component B is [1:9]-[9:1]; The aqueous binder is used in the negative electrode of the lithium battery, and the component B adsorbs the silicon-based negative electrode material of the negative electrode through hydrogen bonds and covers the surface of the silicon-based negative electrode material to form a passivation layer.
2. The water-based adhesive according to claim 1, characterized in that: The component A specifically includes: one or more of sodium carboxymethyl cellulose, polyacrylic acid, sodium alginate, polyvinyl alcohol, and carboxymethyl chitosan.
3. The water-based adhesive according to claim 1, characterized in that: The component B comprises: one or more of tartaric acid, citric acid, oxalic acid, fumaric acid, maleic acid and malic acid.
4. A method for preparing the water-based binder according to any one of claims 1 to 3, characterized in that: The preparation method comprises: Component A is prepared into an aqueous solution with a mass fraction of 1% to 5%, and then a certain amount of component B is added, and the mixture is heated and stirred in a water bath to be uniformly mixed to obtain a mixed solution; The mixed solution is placed in a container with a polytetrafluoroethylene substrate, and placed in a vacuum drying oven for drying to obtain a block precursor; The block precursor is put into a mortar, ground and sieved to obtain a water-based binder.
5. The preparation method according to claim 4, characterized in that: The component A is a polymer containing carboxyl and hydroxyl groups in the molecular formula, specifically including: sodium carboxymethyl cellulose, polyacrylic acid, sodium alginate, polyvinyl alcohol, carboxymethyl chitosan or one or more thereof. The component B is a small molecule organic acid containing a carboxyl group or a hydroxyl group in the molecular formula, specifically including: one or more of tartaric acid, citric acid, oxalic acid, fumaric acid, maleic acid, and malic acid; The mass ratio of the component A to the component B in the mixed solution is [1:9]-[9:1].
6. The preparation method according to claim 4, characterized in that: The drying conditions are as follows: drying in a vacuum drying oven at 90°C-120°C for 5 hours-8 hours; The conditions for the water bath heating and stirring are specifically: the heating temperature is 85° C.-95° C., and the time is 6 hours-10 hours.
7. A negative electrode, characterized in that The negative electrode comprises a negative electrode active material, the aqueous binder as described in any one of claims 1 to 3, and a conductive agent.
8. The negative electrode according to claim 7, characterized in that The negative electrode active material is a silicon-based negative electrode material, specifically including any one of nano-silicon, silicon-carbon composite material, and silicon oxide; the conductive agent includes one or more of acetylene black, carbon nanotubes, Ketjen black, conductive graphite, and graphene; The mass percentages of the negative electrode active material, the conductive agent, and the aqueous binder are [80%-95%]:[3%-10%]:[2%-10%].
9. A lithium battery, characterized in that: The lithium battery comprises a positive electrode, the negative electrode as claimed in claim 7, an electrolyte or a solid electrolyte, and a separator.
10. The lithium battery according to claim 9, characterized in that: The lithium battery includes any one of a lithium-ion battery, a lithium-sulfur battery, and an all-solid-state battery.
Citation Information
Patent Citations
Method for preparing cross-linking waterborne adhesive for lithium ion batteries
CN107793967A
PAA-CA composite-phase binding agent and preparation method thereof
CN110323445A
Three-dimensional network type aqueous binder, preparation method thereof and electrode plate
CN111540903A
Aqueous binder for lithium ion battery, electrode plate and preparation method of electrode plate
CN111883774A
Cited By
Multifunctional amide structure monomer-based silicon-based negative electrode binder and application thereof in lithium / sodium battery
CN121555117A
Multifunctional amide structure monomer-based silicon-based negative electrode binder and application thereof in lithium / sodium batteries
CN122542164A